Targeting the differential addiction to anti-apoptotic BCL-2 family for cancer therapy - Akane Inoue-Yamauchi (Nature Portfolio, 2017)
Small cell lung cancer cells (SCLC) are differentially sensitive to inhibitors of the BCL-2 family. Here the authors analyse the response to BH3 mimetics in SCLC, delineate patterns of expression of apoptotic proteins correlated with differential sensitivities and demonstrate a synergistic anti-tumour activity between ABT-199 and anthracyclines or CDK9 inhibitors.